(untitled) (Prilozi za orijentalnu filologiju, 2017)
Islamic tradition, relying on the Holy Text and Its interpretations, from which many traditions developed, keeps a memory of the uninterrupted line of those who brought God’s word to mankind as the most perfect creation. Although the prophets and the messengers about whom the Qur’an testifies carried their mission in their own time and place, the traditions about them testify to the continuity of God’s messages, and thus the symbolism of these traditions stays alive; from it the inspiration and the doctrine can be drawn by the followers of Muhammad, the first created and the last sent Messenger, with whom the mark of the prophetic, or Muhammad’s light, begins and ends – through a line of his predecessors in the earthly prophetic mission. In this work we registered and brought in the Latin transliteration and Bosnian translation of a selection of verses from ghazals, qasidas, ilahis, terci-i bends, terkib-i bends and lugazs of Bosniak diwan poets from 16th to 19th centuries where God’s prophets and messengers were mentioned, indicating the breaking moments of their lives and their basic traits which kept the actuality of God’s exemplification in the chosen man, as an original and imperishable marks, sign-posts that will last as long as those who can read them and read them in themselves last. Here we mention the most frequent names of the prophets in Diwan poetry, and we give several verses to each mentioned prophet, and in them some of the sequences from their lives are pointed out. These sequences point to the lives of the first expelled prophet sent to mankind – Adam, to Suleiman, a fair and wise ruler and the owner of the ring, who ruled over humans, jinns, birds and who controlled the wind; Ya’kub who mourned his lost son who was dearer to him than anything given in the world; beautiful Yusuf who had to be thrown into the darkness of the well in the very beginning of his journey to become a slave, a captive and finally a ruler; Isa, son of Maryam, who was risen as a Word of God, to enliven the dead and painful human souls “differently”; Musa who spoke with God on Sinai. The remembrances of the mentioned prophetic persons, as well as of Ibrahim and his sons Ismail and Ishak, of Nuh, of Eyyub’s suffering and patience, for the learned Diwan poet were an alchemy that gives to the attentive reader with an open mind and heart a spiritual education (edeb) through literature (edebiyat).